Performance Investigation of WDM based hybrid RF-FSO Link with Unmanned Aerial Vehicles based Optical Relays. Issue 1 (1st September 2022) - Verma, Deepika; Bosu, Rahul; Prince, Shanthi
Abstract: The paper presents the design of wavelength division multiplexing (WDM) based hybrid radio frequency-free space optical communication (RF-FSOC) system for high data rate transmission in the scenarios where the direct line-of-sight (LOS) view between the end-to-end communication nodes is unavailable. As such, a simulation model of unmanned aerial vehicle (UAV) based parallel relaying mechanism incorporating amplify and reflection (AR) technique is presented for establishing a point-to-point FSOC link between UAV and ground base station. Furthermore, the power spectral characteristics of the WDM optical signals modulated by 8-PAM signalling scheme at the transmitter node of the proposed model is simulated and analysed in the Optisystem 16. The simulation results illustrate that the overall link length of the proposed UAV based hybrid system with 1 Gbps data rate and transmitted beam divergence angle of 10 mrad extends upto a maximum range of 200 m in light fog condition.